The nose knows: Foreignness and fortune in China - CALLAHAN, William A. (Institutional Knowledge at Singapore Management University, 2024)
There are so many different kinds of noses. But what can they tell us? Can they be political? Throughout history, noses have been used to separate Chinese people from foreigners. In the present day, can noses also be the key to changing your destiny? If we know more about noses, maybe we can better understand how China sees itself, and its increasingly important place in the world.